Japan, opposing viewpoints - Dudley, William, 1964- (San Diego, CA : Greenhaven Press, 1989)
Presents opposing viewpoints regarding Japan's business practices, society, position as a world power, and relationship with the United States. Includes critical thinking skills activities.
Includes bibliographical references (p. 254-256).
Keywords: Industrial policy -- Japan; Critical thinking; Japan -- Foreign relations -- 1945-1989.; Japan -- Social conditions -- 1945-; Japan